Need and scope for revival of Indian banking and insurance sector in post covid-19 period: A conceptual study - KAMAT, ABHAY; KATKE, DR. KADAMBINI (The journal of contemporary issues in business and government, 2021)
Covid-19 widely known as (Corona Virus) had its fair share in disrupting the overall economic activities across the globe and so is in India. Banking and insurance sector largely regulate economic activities. In India, most of the economic activities are backed by the diversified small, medium, and big monetary institutions. As the economic witnessed standstill during lockdown, corporate and retail clients had posed credit risk for banks. Information technology and digitalized payment options supported in smooth transition and aided business continuity. Insurance as a commodity has gained prominence during and aftermath of the pandemic. Prior to the healthcare crisis, only 10 percent of people in India bought health insurance, now 71 percent and above people consider health insurance is necessary weapon to fight against the unforeseen pandemics like Covid-19. At this stage, it is important to understand the impact of such emergencies on banking and insurance sector to enable appropriate revival strategies to assure required economic support for business and country at large. This conceptual paper attempts to review and analyze the need for and revival strategies adopted in the banking and insurance sector. Framework for the study is built based on online and off-line literature review and the corporate white papers published. Further this study proposes strategies to fill the gap between economic need and operational functioning of the sectors. The scope of this paper would be to throw some light on the challenges faced by banking in the form of credit risk, NPA’s and Insurance sector in India and the measures for sustainable future.